Islamic Republic of Afghanistan : Technical Assistance Report-Strengthening Oversight over State-Owned Corporations, PPPs and Fiscal Risks. (IMF Staff Country Reports; Country Report ;, 2021)
This remote mission provided the authorities with advice in fiscal risk management. The mission covered three interrelated topics: (i) the Public Finance and Expenditure Management (PFEM) Law and fiscal risks oversight and management; (ii) the Stated-Owned Corporations (SOC); and (iii) the Public-Private Partnerships (PPP). This report focuses especially on reforms that could be implemented during the life of the next IMF program.